A paired conceptual framework integrating information systems research and democracy theory - Anastasiadou, Maria (2022)
Anastasiadou, M., dos Santos, V. D., & Evans, A. M. (2020). A paired conceptual framework integrating information systems research and democracy theory. In H. Santos, G. V. Pereira, M. Budde, S. F. Lopes, & P. Nikolic (Eds.), Science and Technologies for Smart Cities: 5th EAI International Summit, SmartCity360, Braga, Portugal, December 4-6, 2019, Proceedings (pp. 217-235). (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST; Vol. 323 LNICST). Springer. https://doi.org/10.1007/978-3-030-51005-3_20